2023
DOI: 10.1051/0004-6361/202245658
|View full text |Cite
|
Sign up to set email alerts
|

Massive pre-main-sequence stars in M17

Abstract: Context. Recently much progress has been made in probing the embedded stages of massive star formation, pointing to formation scenarios that are reminiscent of a scaled-up version of low-mass star formation. However, the latest stages of massive-star formation have rarely been observed, as young massive stars are assumed to reveal their photospheres only when they are fully formed. Aims. Using first and second overtone CO bandhead emission and near- to mid-infrared photometry, we aim to characterize the remnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…These studies found that the Brγ emission can be consistent with magnetospheric accretion, but in several Herbig Ae/Be stars the emitting region extends well beyond the magnetospheric accretion region (located typically below 0.1 au), where the line profiles suggest an additional contribution from material in Keplerian rotation at the base of the disk wind and/or from an inner hot gaseous disk (Caratti o Garatti et al 2015;Mendigutía et al 2015;Hone et al 2019). CO overtone emission is generally attributed to a hot (T ∼ 2000-3000 K) and dense (N CO ∼ 10 21 -10 22 cm −2 ) inner disk inside the dust sublimation radius (e.g., Ilee et al 2014;Lyo et al 2017;Poorta et al 2023).…”
Section: Physical Origin Of the Co Overtone And Brγ Emission Inmentioning
confidence: 99%
“…These studies found that the Brγ emission can be consistent with magnetospheric accretion, but in several Herbig Ae/Be stars the emitting region extends well beyond the magnetospheric accretion region (located typically below 0.1 au), where the line profiles suggest an additional contribution from material in Keplerian rotation at the base of the disk wind and/or from an inner hot gaseous disk (Caratti o Garatti et al 2015;Mendigutía et al 2015;Hone et al 2019). CO overtone emission is generally attributed to a hot (T ∼ 2000-3000 K) and dense (N CO ∼ 10 21 -10 22 cm −2 ) inner disk inside the dust sublimation radius (e.g., Ilee et al 2014;Lyo et al 2017;Poorta et al 2023).…”
Section: Physical Origin Of the Co Overtone And Brγ Emission Inmentioning
confidence: 99%